USE OF GONADORELIN IN HANDLING DELAYED PUBERTY IN BALI CATTLE - Chandra, Anak Agung Adhitya; Trilaksana, I Gusti Ngurah Bagus; Pemayun, Tjok Gde Oka (Buletin Veteriner Udayana, 2022)
Delayed puberty is one of the problems faced by breeders, causing delays in production. Several hormones have been used in handling cases of delayed puberty. Purpose of this research was to determine the use of gonadorelin in dealing with delayed puberty in balinese cattle. Balinese cattle used in this reasearch are female balinese cattle age 24 month or more which havent showed any sign of the first estrus (puberty). Female balinese cattle was divided into 2 groups each consist 16 cattles. Both groups given the treatment which is gonadorelin injection dose 50 ?g/cattle (P1/Group 1) and 100 ?g/cattle (P2/Group 2). Observations for follicular diameter were made by ultrasound before gonadorelin injection and after the signs of estrus were showed. Observation for the estrus signs and its intensity were done twice a day which are at 06.00 – 08.00 WITA and 17.00 – 19.00 WITA. The results showed that the average follicular diameter before the gonadorelin injection were P1  = 4,38mm and P2 = 4,41mm meanwhile after the estrus showed up, the average follicular diameter became P1 = 7,68mm and P2 = 10,83mm. The average time of emergence of estrus at P1 = 6,38 days while P2 = 4 days, while the intensity of estrus at P1 = 1,5 days and P2 = 2,56 days. Statistically the difference in diameter before treatment was not significant (p> 0.05) while during estrus there was a significant difference (p <0.05) between the two treatments. At the time of emergence of estrus and estrus intensity there were no statistically significant differences (p> 0.05) between the two treatments. For the conclusion, administration of gonadorelin can stimulate follicular development and cause the emergence of estrus in Balinese Cattle  that experience delayed puberty.